Galleria mellonella Larvae as an Infection Model to Investigate sRNA-Mediated Pathogenesis in Staphylococcus aureus - Ménard, Guillaume; Rouillon, Astrid; Ghukasyan, Gevorg; Emily, Mathieu; Felden, Brice; Donnio, Pierre-Yves (Frontiers in Cellular and Infection Microbiology, 2021)
Small regulatory RNAs (sRNAs) are key players in bacterial regulatory networks. Monitoring their expression inside living colonized or infected organisms is essential for identifying sRNA functions, but few studies have looked at sRNA expression during host infection with bacterial pathogens. Insufficient in vivo studies monitoring sRNA expression attest to the difficulties in collecting such data, we therefore developed a non-mammalian infection model using larval Galleria mellonella to analyze the roles of Staphylococcus aureus sRNAs during larval infection and to quickly determine possible sRNA involvement in staphylococcal virulence before proceeding to more complicated animal testing. We began by using the model to test infected larvae for immunohistochemical evidence of infection as well as host inflammatory responses over time. To monitor sRNA expression during infection, total RNAs were extracted from the larvae and invading bacteria at different time points. The expression profiles of the tested sRNAs were distinct and they fluctuated over time, with expression of both sprD and sprC increased during infection and associated with mortality, while rnaIII expression remained barely detectable over time. A strong correlation was observed between sprD expression and the mortality. To confirm these results, we used sRNA-knockout mutants to investigate sRNA involvement in Staphylococcus aureus pathogenesis, finding that the decrease in death rates is delayed when either sprD or sprC was lacking. These results demonstrate the relevance of this G. mellonella model for investigating the role of sRNAs as transcriptional regulators involved in staphylococcal virulence. This insect model provides a fast and easy method for monitoring sRNA (and mRNA) participation in S. aureus pathogenesis, and can also be used for other human bacterial pathogens.